Effect Of Led Exposure Time On The Temperature Rise, Depth Of Cure And Microhardness Of Nanohybrid Composite Resin - Olivia Nauli Komala; Ednanisa Budianto; Yosi Kusuma Eriwati; Siti Triaminingsih (Universitas Muhammadiyah Yogyakarta, 2012)
It has been reported that depth of cure of composite resin can be achieved by prolonged light curing but causing temperature rise that could harm the pulp and resulted uncomfortable condition to patient. Objectives: To evaluate the effect of light-emitting-diode (LED) light curing unit on the temperature rise, depth of cure and microhardness of nanohybrid composite resin. Materials and Methods: Sixty specimens of nanohybrid composite resin (Tetric N Ceram, Ivoclar-Vivadent, Lichtenstein) with diameter of 5 mm, thickness of 5 mm were divided into 3 groups: Group I (n=20) were light-cured for 15 seconds, Group II (n=20) for 20 seconds, Group III (n=20) for 40 seconds using LED light curing unit (Hilux/Ledmax, Japan). The temperature rise was measured using digital thermometer at initial time to the highest temperature peak. The depth of cure was measured by scraping method. Microhardness was determined using Vickers Microhardness Tester at each 1 mm depth of the composite resin. Data were analyzed using Kruskal-Wallis and Mann-Whitney tests. Results: There were significant differences on temperature rise, depth of cure and hardness of nanohybrid composite resin at each 1 mm depth after light exposure time of 15, 20, and 40 seconds. The highest depth of cure was achieved after curing for 40 seconds but the highest microhardness was achieved after curing for 20 seconds at 1 mm from the top of specimens. Conclusion: Exposure time of 20 seconds produced low temperature rise, depth of cure and the highest VHN than the other exposure time.